Preparedness of Special Schools in Banda Aceh Towards Earthquake and Tsunami Disasters - Jummi, Cut Vita Rajiatul; Desfandi, Mirza; Maghfirah, Fuja; Diah*, Husna; Yulianti, Fitriani; Pilay, Karishma Kavita (Universitas Syiah Kuala, 2024)
People with disabilities are a group at high risk during a disaster, due to limited abilities and access to the physical environment, information and communication in the community. The purpose of this study was to determine the level of preparedness of students and teachers as well as facilities of Special School in Banda Aceh towards earthquake and tsunami disasters. Data was collected using observation and survey methods using a standardized questionnaire developed by IIS-UNESCO/ISDR, then processed using index analysis. The results of the research on student preparedness were in the ready category, while teacher preparedness showed very ready results with parameters: knowledge and attitude category, emergency response plan category, disaster warning system category, and resource mobilization. Facilities at special schools are generally available in good condition. Although the preparedness of students, teachers and facilities tends towards the acceptable level, it is very important to socialize and simulate the disaster preparedness and increase the capacity to deal with earthquake and tsunami disasters that cannot be predicted when they will occur